TEKNOLOGI TEPAT GUNA DAN DIGITALISASI KEUANGAN BAGI UMKM CENDOL DAWET DI TULUNGAGUNG - Danang Erwanto; Lina Saptaria; Iska Yanuartanti; Yoga Pebri Aprilia; Naili Sa'adatin Najwa (Universitas Mataram, 2026)
This Community Service Program aims to strengthen the capacity and sustainability of the Cendol Dawet micro-enterprise under the Era Muda Berjaya Group in Tulungagung through the implementation of appropriate technology and financial digitalization. The main problems faced by the partner include manual production processes that limit capacity and product consistency, as well as the absence of a digital financial system that hinders accurate profit margin monitoring. The program involved several stages: socialization, training, the application of an automatic cendol mixer and extruder machine, digital bookkeeping assistance, and continuous evaluation. The results showed a 33% increase in production capacity through the application of appropriate technology and standardized operating procedures. In financial management, the partner successfully implemented a simple digital bookkeeping system using Excel templates, enabling separation of household and business finances and accurate calculation of a 20% average profit margin per product. The adoption of financial digitalization has improved efficiency, transparency, and decision-making processes. Overall, this program demonstrates that the synergy between appropriate technology and financial digital transformation can enhance productivity, professionalism, and sustainability of traditional culinary-based MSMEs.